ANTIDEPRESSANT-ASSOCIATED SEXUAL DYSFUNCTION (AASD) – FROM PATHOPHYSIOLOGY TO CLINICAL MANAGEMENT: A LITERATURE REVIEW - Agnieszka Kurek; Radosław Krzysztof Binkowski; Rafał Bednarczyk; Natalia Bednarczyk; Natalia Krajewska; Aleksandra Lejman; Aleksandra Mazurkiewicz; Hubert Sidor; Monika Wołosik; Szymon Zysiak (International Journal of Innovative Technologies in Social Science, 2026)
Major Depressive Disorder (MDD) presents a global challenge, with pharmacotherapy based on SSRIs and SNRIs remaining the standard of care. Despite clinical efficacy, the tolerability of these agents is often limited by iatrogenic Antidepressant-Associated Sexual Dysfunction (AASD), a leading cause of therapeutic non-adherence and so-called "hidden non-compliance," resulting in disease relapse. This paper provides a comprehensive literature review aimed at updating knowledge on epidemiology, neurobiological mechanisms extending beyond the serotonin hypothesis, and modern management strategies for AASD, with particular emphasis on Post-SSRI Sexual Dysfunction (PSSD). Databases including PubMed, ScienceDirect, Cochrane Library, and Google Scholar were searched, focusing on studies utilizing validated psychometric tools (e.g., ASEX, PRSexDQ). The analysis reveals a significant disparity between spontaneously reported AASD rates (10–15%) and those detected via screening (70–80%). A risk hierarchy was confirmed: paroxetine and venlafaxine demonstrate the highest iatrogenic potential, attributed partly to nitric oxide synthase inhibition and dopaminergic suppression. Vortioxetine and bupropion are characterized by a neutral profile, offering a safe alternative. The review also confirms the growing clinical importance of PSSD as a persistent complication. AASD requires proactive monitoring in daily practice. Results support moving away from a "wait and see" strategy in favor of routine screening and early implementation of switching or augmentation strategies. Personalization of pharmacotherapy is crucial for maintaining patient adherence and ensuring long-term depression treatment efficacy.